2010
DOI: 10.1002/bit.22914
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning and characterization of electrospun poly(ε‐caprolactone)/gelatin nanofiber tissue scaffolds by femtosecond laser ablation for tissue engineering applications

Abstract: Experimental investigations aimed at assessing the effectiveness of femtosecond (FS) laser ablation for creating microscale features on electrospun poly(ε-caprolactone) (PCL)/gelatin nanofiber tissue scaffold capable of controlling cell distribution are described. Statistical comparisons of the fiber diameter and surface porosity on laser-machined and as-spun surface were made and results showed that laser ablation did not change the fiber surface morphology. The minimum feature size that could be created on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 48 publications
(50 reference statements)
3
81
0
Order By: Relevance
“…Importantly, this approach permits the combination of two well-known triggers of cell alignment that have usually been studied individually. Micropatterned structures have been incorporated on electrospun membranes of polyurethanes or PCL/gelatine blends using either femtosecond-pulse laser ablation (Lim et al 2011) or silicone moulds patterned with soft lithography (Dempsey et al 2010). Both methods resulted in the generation of sharp surface topographies of varying groove widths and depths of 20-500 μm, depending on the method.…”
Section: Substrate Characterizationmentioning
confidence: 99%
“…Importantly, this approach permits the combination of two well-known triggers of cell alignment that have usually been studied individually. Micropatterned structures have been incorporated on electrospun membranes of polyurethanes or PCL/gelatine blends using either femtosecond-pulse laser ablation (Lim et al 2011) or silicone moulds patterned with soft lithography (Dempsey et al 2010). Both methods resulted in the generation of sharp surface topographies of varying groove widths and depths of 20-500 μm, depending on the method.…”
Section: Substrate Characterizationmentioning
confidence: 99%
“…Lim et al demonstrated that a femtosecond laser can be used to fabricate arbitrary patterns and pattern arrays on freestanding electrospun polycaprolactone membranes for use as functional tissue scaffolds. 29 Melissinaki et al reported the production of three-dimensional scaffolds of polylactide-based materials through layer-by-layer multiphoton polymerization. 30 Ovsianikov et al used the two-photon polymerization …”
Section: O R I G I N a L R E S E A R C Hmentioning
confidence: 99%
“…Lim et al demonstrated that a femtosecond laser can be used to fabricate arbitrary patterns and pattern arrays on freestanding electrospun polycaprolactone membranes for use as functional tissue scaffolds. 29 Melissinaki et al reported the production of three-dimensional scaffolds of polylactide-based materials through layer-by-layer multiphoton polymerization. 30 Ovsianikov et al used the two-photon polymerization method to fabricate three-dimensional computer-designed scaffolds on photosensitive methacrylamide-modified gelatin.…”
Section: Introductionmentioning
confidence: 99%